Criminal Law Enforcement against Violations of Non-Smoking Areas Based on Law Number 17 of 2023 concerning Health - Dhiyo Hadi; Erikson Sihotang; Nyoman Suandika (CV. Syntax Corporation Indonesia, 2024)
Legal protection for consumers against the dangers of smoking in Indonesia is still very minimal, especially regarding law enforcement in smoking ban areas. This study aims to analyze legal protection for consumers against the dangers of smoking and evaluate the effectiveness of law enforcement against violations in smoking ban areas. This research uses normative research methods supported by empirical research. Data was collected through analysis of legislation and related literature, as well as observation of law enforcement practices in the field. The research found that legal protection of consumers is divided into two aspects, namely preventive and repressive. However, there are three factors inhibiting law enforcement in smoking ban areas, namely the lack of clear legal substance, low understanding among law enforcement, and lack of supporting infrastructure. The results of this study show that although there are regulations governing smoking restrictions, their implementation is still weak. Collaborative efforts between the government, communities, and businesses are needed to increase awareness and compliance with existing regulations.